A Comprehensive Review on Biotransformation, Interaction, and Health of Gut Microbiota and Bioactive Components - Zhang, Lin; Ma, Xiao-Gen (Combinatorial Chemistry & High Throughput Screening, 2024)
Background: The relationship between gut microbiota and bioactive components has become the research focus in the world. We attempted to clarify the relationship between biotransformation and metabolites of gut microbiota and bioactive components, and explore the metabolic pathway and mechanism of bioactive ingredients in vivo, which will provide an important theoretical basis for the clinical research of bioactive ingredients and rationality of drugs, and also provide an important reference for the development of new drugs with high bioavailability. Methods: The related references of this review on microbiota and bioactive components were collected from both online and offline databases, such as ScienceDirect, PubMed, Elsevier, Willy, SciFinder, Google Scholar, Web of Science, Baidu Scholar, SciHub, Scopus, and CNKI. Results: This review summarized the biotransformation of bioactive components under the action of gut microbiota, including flavonoids, terpenoids, phenylpropanoids, alkaloids, steroids, and other compounds. The interaction of bioactive components and gut microbiota is a key link for drug efficacy. Relevant research is crucial to clarify bioactive components and their mechanisms, which involve the complex interaction among bioactive components, gut microbiota, and intestinal epithelial cells. This review also summarized the individualized, precise, and targeted intervention of gut microbiota in the field of intestinal microorganisms from the aspects of dietary fiber, microecological agents, fecal microbiota transplantation, and postbiotics. It will provide an important reference for intestinal microecology in the field of nutrition and health for people. Conclusion: To sum up, the importance of human gut microbiota in the research of bioactive components metabolism and transformation has attracted the attention of scholars all over the world. It is believed that with the deepening of research, human gut microbiota will be more widely used in the pharmacodynamic basis, drug toxicity relationship, new drug discovery, drug absorption mechanism, and drug transport mechanism in the future.
Keywords: Gut microbiota